2020
DOI: 10.1136/bmjdrc-2019-000989
|View full text |Cite
|
Sign up to set email alerts
|

Superior socioeconomic status in patients with type 2 diabetes having gastric bypass surgery: a case-control analysis of 10 642 individuals

Abstract: IntroductionThe incidence of type 2 diabetes mellitus (T2DM) is increasing, in parallel with the epidemic of obesity. Although bariatric surgery, which profoundly affects T2DM, has increased 10-fold since the millennium, only a fraction of diabetics is offered this treatment option.ObjectiveTo investigate the association between clinical and socioeconomic factors in selecting patients with T2DM for bariatric surgery in a publicly financed healthcare system.Research design and methodsCohort study using prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The hyperglycemic microenvironment caused by diabetes exacerbates damage of osteoblasts. Chronic inflammation in diabetic patients inhibits the activity of stem cells and increases calcium excretion [ 1 , 34 , 35 ]. Additionally, the interaction of hyperglycemia with parathyroid hormone and the vitamin D system weakens bone turnover in diabetic patients and reduces osteocalcin produced by osteoblasts [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hyperglycemic microenvironment caused by diabetes exacerbates damage of osteoblasts. Chronic inflammation in diabetic patients inhibits the activity of stem cells and increases calcium excretion [ 1 , 34 , 35 ]. Additionally, the interaction of hyperglycemia with parathyroid hormone and the vitamin D system weakens bone turnover in diabetic patients and reduces osteocalcin produced by osteoblasts [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… 31 Chronic hyperglycemia causes chronic damage to various tissues and organs of the body, which results in various diabetic complications, especially in the eyes, kidneys, blood vessels, and bones. 32 , 33 , 34 Among them, diabetic osteoporosis refers to the metabolic bone disease that occurs because of the hyperglycemic microenvironment. 32 Recent studies have shown that insulin deficiency or tolerance in diabetic patients leads to disruptions of glucose, lipid, and calcium metabolisms, which results in dysfunctional osteoblasts and osteoclasts and ultimately causes systemic bone loss and a reduction in bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 , 34 Among them, diabetic osteoporosis refers to the metabolic bone disease that occurs because of the hyperglycemic microenvironment. 32 Recent studies have shown that insulin deficiency or tolerance in diabetic patients leads to disruptions of glucose, lipid, and calcium metabolisms, which results in dysfunctional osteoblasts and osteoclasts and ultimately causes systemic bone loss and a reduction in bone mineral density. 35 , 36 Additionally, hyperglycemic microenvironment‐induced autophagy adversely affects the proliferation and differentiation of osteoblasts, which is associated with increases in fracture risk and bone mineral density loss in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperglycemic microenvironment caused by diabetes exacerbates damage of osteoblasts. Chronic inflammation in diabetic patients inhibits the activity of stem cells and increases calcium excretion [1,32,33]. Additionally, the interaction of hyperglycemia with parathyroid hormone and the vitamin D system weakens bone turnover in diabetic patients and reduces osteocalcin produced by osteoblasts [34,35].…”
Section: Discussionmentioning
confidence: 99%